Pathogen-specific epitopes as epidemiological tools for defining the magnitude of Mycobacterium leprae transmission in areas endemic for leprosy - Martins, Marcia V. S. B. (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Microbiologia Celular. Rio de Janeiro, RJ, Brasil.